2009 Workshop on Network Coding, Theory, and Applications 2009
DOI: 10.1109/netcod.2009.5191400
|View full text |Cite
|
Sign up to set email alerts
|

Some results on communicating the sum of sources over a network

Abstract: Abstract-We consider the problem of communicating the sum of m sources to n terminals in a directed acyclic network. Recently, it was shown that for a network of unit capacity links with either m = 2 or n = 2, the sum of the sources can be communicated to the terminals if and only if every source-terminal pair is connected in the network. We show in this paper that for any finite set of primes, there exists a network where the sum of the sources can be communicated to the terminals only over finite fields of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…Primarily we show that the characterization of [7] no longer holds when the number of sources and terminals is greater than two. We note that a similar result was obtained recently in an independent manner by [6]. We then turn to obtain encoding schemes for the three source three terminal case (3s/3t).…”
Section: Introductionsupporting
confidence: 76%
“…Primarily we show that the characterization of [7] no longer holds when the number of sources and terminals is greater than two. We note that a similar result was obtained recently in an independent manner by [6]. We then turn to obtain encoding schemes for the three source three terminal case (3s/3t).…”
Section: Introductionsupporting
confidence: 76%
“…Such networks have been given the name sum-networks. In [11] it was shown that for any finite set of primes there exists a sum-network which has a vector linear solution for any vector dimension if and only if the characteristic of the finite field belongs to the given set. In [12] it was shown that for any sum-network, there exists a multiple-unicast network which has a rate 1 solution if and only if the sum-network has a rate 1 solution.…”
Section: Introductionmentioning
confidence: 99%
“…ANALYSIS OF CASE 3 We now prove Theorem 1 under the assumption that G has no nodes of type (3, 3), (2,3) and (3,2). Note that the node labeling procedure presented above assigns a label (c s (v), c t (v)) to a node v where c s (v) (c t (v)) is the number of sources (terminals) that v is connected to.…”
Section: B Case Analysismentioning
confidence: 94%
“…. 3, such that it does not have any (3,3), (2,3) or (3, 2) nodes. There does not exist an edge between (2, 2) nodes of different color in G.…”
Section: B Case Analysismentioning
confidence: 99%
See 1 more Smart Citation